Analisis minat siswa setelah lulus Sekolah Menengah Kejuruan (Studi Kasus SMK Negeri 2 Parepare) - Akshari Tahir Lopa; Anas Arfandi; Jan Robert E. Salim (Seminar Nasional LP2M UNM, 2019)
Graduates of vocational high school (SMK) are prepared to work, further study, and be an entrepreneurship. This study aims to describe the interests of students of Parepare Vocational High School State 2 after graduating, are they interested in working, continuing study, or be an entrepreneur? To answer these questions, the study was conducted by collecting data using a questionnaire. The population of the study was all students of class XII of Parepare Vocational High School State 2, and the sample used cluster random sampling with a total sample of 166 respondents. The results of the study show that 1) the students of Parepare Vocational High School State 2 were interested to work and it dominantly in the High category; 2) the students of Parepare Vocational High School State 2 whom interest to continue their studies, dominantly in the Very High category; 3) the interest of Parepare Vocational High School State 2 students in an entrepreneurship dominantly in the High category; and 4) vocational students are dominantly interested in continuing their studies at a higher level of 61%, while 23% are interested in working, and the remaining 16% are interested in entrepreneurship.